Business and professional communication in a digital age - Waldeck, Jennifer H.; Kearney, Patricia; Plax, Timothy G. (Wadsworth/ Cengage Learning, 2013)
It's the quintessential book on 21st-century business and professional communication. The authors succeed in pulling together layers and layers of integrated business communication concepts, topics, issues, and broad competencies at the heart of professional excellence.